The lake cod Gadus morhua kildinensis in the context of conservation biology - Igor Popov (Water Biology and Security)
Atlantic cod, Gadus morhua, is a marine fish, but there are several Arctic lakes, where it also occurs. Mogilnoye Lake on Kildin Island in the Barents Sea is especially famous for them. It is a salinity stratified meromictic lake. The surface layer is fresh with saline water saturated with hydrogen sulfide underneath. Kildin cod have been studied over the last 100 years with emphasis on taxonomy, physiology, genetics and growth. However, the conservation of this species has been overlooked. Recent sonar surveys showed that the cod are quite abundant, but in danger from hydrogen sulfide accumulation within the lower lake levels. Therefore, the habitat of this species is shrinking. Conservation studies must be a priority in the situations like this.